The language of Italian television sales - Diadori, Pierangela (Spunti e Ricerche, 2016)
The diffusion of private television networks in Italy during the past decades has seen an increase in the use of television sales. The analysis of a selection of videorecorded programmes (taken from various Italian television networks in 1991) has shown a peculiar mixture of characteristics (oral/written discourse, formal/informal speech, specific/general terms) and a message structuring which reflects the opposite needs of popularisation (due to the audience) and specialisation (due to the products advertised).